Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10815-005-4919-1
|View full text |Cite
|
Sign up to set email alerts
|

Lower embryonic loss rates among twin gestations following assisted reproduction

Abstract: Purpose : To determine whether maternal age and number of transferred embryos influence early pregnancy losses in twin pregnancies compared to singletons following IVF/ICSI. Methods : We compared the pregnancy loss rates in singleton (n = 549) and twin (n = 252) gestations, stratified by maternal age (≤35 and >35 years) and the number of transferred embryos (1-3 and 4-9). Results : Loss rates of singleton pregnancies were significantly higher than that in twins (OR 3.0, 95% CI 1.9, 4.9), especially among singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Assisted-reproduction twin pregnancies have reduced spontaneous EPL rates compared with assisted-reproduction singleton pregnancies and in particular after IVF/ICSI treatment (La Sala et al, 2005;Miró et al, 2012;Tummers et al, 2003). A recent study has shown that the overall rate of miscarriage is higher for women aged 34 years and that the difference in live-birth rate between twin and singleton pregnancies is 2.4-fold higher in older than in younger women (Miró et al, 2012).…”
Section: Early Pregnancy Loss In Assisted-reproduction Twinsmentioning
confidence: 99%
“…Assisted-reproduction twin pregnancies have reduced spontaneous EPL rates compared with assisted-reproduction singleton pregnancies and in particular after IVF/ICSI treatment (La Sala et al, 2005;Miró et al, 2012;Tummers et al, 2003). A recent study has shown that the overall rate of miscarriage is higher for women aged 34 years and that the difference in live-birth rate between twin and singleton pregnancies is 2.4-fold higher in older than in younger women (Miró et al, 2012).…”
Section: Early Pregnancy Loss In Assisted-reproduction Twinsmentioning
confidence: 99%
“…La Sala et al [12] have reported that spontaneous miscarriage rates are higher in singleton IVF/intracytoplasmic sperm injection (ICSI) pregnancies (OR 5.0; 95% CI 2.2-11.9) compared with twin IVF (OR 3.0; 95% CI 1.9-9.9). They concluded that higher implantation rates could be a reflection of better uterine function.…”
Section: Miscarriagesmentioning
confidence: 99%
“…The study by Lambers et al (15) demonstrated that the total pregnancy loss was 18.5% and 2.5% (P<.001) in singleton and twin gestations, respectively, which is comparable with our results. A study by La Sala et al (17) demonstrated that twins have a significantly lower miscarriage rate compared with singletons after IVF/ ICSI, which the investigators explained by stating that the higher implantation rate represented a better capacity of the uterus for early embryonic development. It is interesting to note that the ''single pregnancy from the start'' group, which was obviously the group with the lowest implantation rate, was the only group who demonstrated a significantly lower number of mature oocytes and 2PN oocytes and had the highest miscarriage rate.…”
mentioning
confidence: 99%